Об электростатической аналогии магнитостатического поля в неоднородной намагничивающейся среде - Михайлов, В.М.; Чунихин, К.В. (Електротехніка і електромеханіка, 2017)
Сделан анализ применения электростатической аналогии в магнитостатике неоднородных намагничивающихся
сред на основе дипольной модели и модели намагничивания молекулярными токами. Показано, что корректным
является использование дипольной модели намагничивания. Получено соотношение между намагниченностями
для различных моделей, поясняющее применение в электростатической аналогии намагниченности молекулярными токами Зроблено аналіз застосування електростатичної аналогії у магнетостатиці неоднорідних магнетованих середовищ
на основі дипольної моделі та моделі намагнечування молекулярними струмами. Показано, що коректним є застосування дипольної моделі намагнечування. Отримано співвідношення між намагнеченостями для різних моделей, котре
пояснює використання в електростатичній аналогії намагнеченості молекулярними струмами. Purpose. The application in electrostatic analogy of magnetostatics for inhomogeneous magnetized media of two known
magnetization models. Methodology. A comparison of basic
equations and formulas of electrostatic and magnetostatic
field in immoveable isotropic inhomogeneous polarized medium for dipole model and the magnetization model by molecular currents is made. The value-analogues for dipole
model of magnetization are established. Results. We have
shown that the using of dipole model of magnetization is correct. There is not even formal analogy with electrostatic field
in the case of using the magnetization model by molecular
currents. The relation between the magnetizations for various
models is obtained. It allows us to justify the using magnetization by molecular currents in electrostatic analogy. Originality. The magnetization for dipole model is introduced and the
possibility of using magnetization by molecular currents in the
formulas for calculating potential magnetostatic field in magnetized medium is substantiated. Practical value. The results
allow to obtain correct formulation and solution of the problem of magnetostatic field calculation in inhomogeneous magnetized medium.